Consumer mobility awareness in information centric networks - Caldeira Hernandez, Diego (2022)
Mobile data traffic is expanding significantly since the surge and evolution of wireless communication technologies, leading to the design and implementation of different types of mobile networks. Information Centric Network paradigms have been pointed as an alternative to bypass the restrictions imposed by the traditional IP Networks, such as the one imposed by the mobility of its users. Despite their potential advantages regarding mobile wireless environments, several significant research challenges remain to be addressed, more specifically the communication damage due to handover, causing loss of packets. The scope of this dissertation is the development of NDN-based mechanisms with support for Consumer mobility in two different communication approaches: single content request and publish-subscribe. The proposed schemes address a remote mobility predictor entity, whose purpose is to monitor and anticipate trajectories, while compelling the infrastructure to adjust to the new paths, resulting in an efficient way to manage the consumers’ mobility with the purpose of attaining a better quality of service to users. The implementation and evaluation of the proposed schemes were performed using ndnSIM, through functional and non-functional scenarios. The latter uses real traces of urban mobility and connectivity. The obtained results show that the proposed solution far surpasses the native NDN workflow and the traditional publish-subscribe solutions with respect to content delivery ratio and network overhead.